Advanced Differential E-Module: Integrating Case-Based and Visual Exploration - Takaendengan, Bertu Rianto; Nuha, Agusyarif Rezka; Damayanti, Taulia; Asriadi; Janna, Miftahul; Anggraini, Fitriana (Journal of Education Technology, 2024)
One of the main challenges in learning advanced calculus is students' difficulty understanding complex concepts and visualizing function graphs, especially in learning partial derivatives. To overcome this challenge, this study focuses on developing an advanced differential e-module that integrates case studies with visual exploration. This study uses the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects are material experts and learning media. The trial subjects are 15 students from the Mathematics Education Study Program. The data collection method uses a questionnaire. The research instruments include an assessment of the validity and practicality of the developed learning media. The techniques used in analyzing the data are qualitative and quantitative descriptive analysis. The study results indicate that this e-module achieves a good level of feasibility, which means that the module is in line with educational objectives and shows a very good level of practicality in the classroom. Students responded positively to its use, especially because of its case-based and visual nature. In addition, for further research, this e-module has the potential to be adapted to other areas of mathematics education by integrating additional technology features and other materials. By enhancing visualization and interactivity, this e-module can significantly enhance students' learning experience in mathematics education.